2005
DOI: 10.1002/qua.20788
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: E.A. Boudreaux and E. Baxter, “More QR‐SCMEH‐MO calculations on group VIB transition metal molecules, M2 (M = Cr, Mo, W, Sg) valence and valence‐core effects,” International Journal of Quantum Chemistry(2004) 100(6)1170–1178

Abstract: The original article to which this Erratum refers was published in International Journal of Quantum Chemistry (2004) 100(6) 1170–1178.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The main reasons for such difficulties may be summarized as follows. 7 The purpose of the present work is to afford an accurate description of the whole potential energy curve for the dimers of molybdenum and tungsten as well as for the heteronuclear CrMo by using multireference perturbation theory in the n-electron valence state perturbation theory ͑NEVPT͒ approach recently developed in our laboratory. Secondly, the nondynamical correlation alone is insufficient to provide a satisfactory description of the potential energy curve because a large part of the bond energy is obtained by taking into account the dynamical correlation of both the external and semi-internal electrons.…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons for such difficulties may be summarized as follows. 7 The purpose of the present work is to afford an accurate description of the whole potential energy curve for the dimers of molybdenum and tungsten as well as for the heteronuclear CrMo by using multireference perturbation theory in the n-electron valence state perturbation theory ͑NEVPT͒ approach recently developed in our laboratory. Secondly, the nondynamical correlation alone is insufficient to provide a satisfactory description of the potential energy curve because a large part of the bond energy is obtained by taking into account the dynamical correlation of both the external and semi-internal electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is anticipated that a significant polarization of valence and valence–core electron densities has occurred in these molecules at such short internuclear separations. In fact, in our previous publication, we showed that valence–core contributions to bond dissociation energies ranged from 16 to 24% for Mo 2 , Cr 2 , and W 2 , respectively 1.…”
Section: Introductionmentioning
confidence: 83%
“…In a recent publication, it was shown that in self‐consistent modified extended Huckel molecular (SCMEH‐MO) calculations on transition‐metal diatomic molecules, there is a non‐insignificant interaction between electrons in valence orbitals, n d , ( n + 1) s , ( n + 1) p , and those in valence–core orbitals, ( n − 1) s and ( n − 1) p 1. Subsequently, this observation was pursued further in depth on a more fundamental basis through the derivation of a modified molecular Hamiltonian explicitly accounting for these interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The Cr 2 and Mo 2 molecules, containing group VIB transition metal atoms, can be both regarded as containing a formal sextuple bond (see Ref. [16] for more details) and have been excellent targets [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] for testing novel ab initio methods. When estimating the quality of theoretical results, the availability of experimental data [6][7][8][9] for these molecules is very important.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of ab initio studies [17,20,21,[23][24][25]28] of the molybdenum dimer in the ground 1 + g state, most of them focusing on the molecular properties at near-equilibrium geometries. A more stringent task is a correct description of the shape of the PEC at geometries that are far from the equilibrium arrangement [32].…”
Section: Introductionmentioning
confidence: 99%